PENGARUH MACAM DAN TAKARAN PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KORO PEDANG PUTIH (Canavalia ensiformis L.) DI TANAH GRUMOSOL - Revisan Prisintava Hia; Yacobus Sunaryo; Maria Theresia Darini (JURNAL ILMIAH AGROUST, 2019)
This research was conducted to determine the kinds and dosage of organic fertilizers on the growth and yield of jack bean cultivated on the grumosol soil. This research was conducted in March - July 2017 at the UPTD Balai Pengembangan Perbenihan Tanaman Pangan dan Holtikultura unit Kerja Gading, Jl. Yogyakarta – Wonosari km 33, located in Gading, Playen, Gunung Kidul district, Special Region of Yogyakarta. It has an altitude of 200 meters above sea level with a daily average temperature of 27.7 oC and relative humidity of 80 - 85%. This research was a field experiment arranged with factorial Randomized Complete Block Design (RCBD) 3 replications. The first factor was the kinds of organic fertilizer consisting of chicken manure, goat manure, cow manure, and green manure of gliriside. The second factor was the dosage of organic fertilizer consisting of 10, 15, and 20 ton.ha-1. Observation variables included plant height, number of leaves, number of flowers.plant-1, dry weight of plants, number of pods.plant-1, and seed weight.ha-1. Data were analyzed by variance at 5% level. The difference between treatments will be tested by the DMRT Multiple Range Test at a level of 5%. The results indicated that there was no interaction between the treatment of kind and dosages of organic fertilizers on the observation variables.Chicken manure application the growth of jack bean plant was not significantly different from the treatment of cow manure and green manure of gliriside, but it could produce better growth than goat manure treatment. Chicken manure yields the seed weight.ha-1 of jack bean plants not significantly different from green manure treatment, but could produce growth than goat and cow manure treatment. Dosage 10, 15, and 20 ton.ha-1 resulted growth and yield of jack bean not significantly different